2020
DOI: 10.1016/j.jcv.2020.104681
|View full text |Cite
|
Sign up to set email alerts
|

First performance report of QIAreach™ Anti-SARS-CoV-2 Total Test, an innovative nanoparticle fluorescence digital detection platform

Abstract: Highlights The QIAreach™ Anti-SARS-CoV-2 Total Test (Anti-CoV2) is a rapid, qualitative serological test. Anti-CoV2 uses nanoparticle fluorescence technology to detect total antibody against SARS-CoV-2. Anti-CoV2 had 100 % sensitivity (PPA; 95 % CI 88.4–100 %) and 100 % specificity (NPA; 95 % CI 95.2–100 %). No cross-reactivity observed with seasonal coronaviruses or other respiratory pathogens tested. Anti-CoV2 provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…The high level of agreement observed in this study is consistent with the performance reported by the manufacturer [ 27 ], and significantly expands upon the number of clinical specimens used in the previous evaluation. In contrast, the pooled sensitivity calculated in a meta-analysis of other anti-SARS-CoV-2 LFIAs was 66.0% (95% CI: 49.3 to 79.3) [ 9 ].…”
Section: Discussionsupporting
confidence: 89%
“…The high level of agreement observed in this study is consistent with the performance reported by the manufacturer [ 27 ], and significantly expands upon the number of clinical specimens used in the previous evaluation. In contrast, the pooled sensitivity calculated in a meta-analysis of other anti-SARS-CoV-2 LFIAs was 66.0% (95% CI: 49.3 to 79.3) [ 9 ].…”
Section: Discussionsupporting
confidence: 89%
“…Hu et al found that EDTA-K2 could chelate with colloidal gold, and the chelated colloidal gold was adsorbed on a conjugate release pad, which significantly improved the sensitivity and specificity of the diagnosis (Hu et al, 2021). Stieber et al reported an LFIA detection device using fluorescent nanoparticles as a signal for antibodies against SARS-CoV-2, showing 100% specificity and sensitivity by qualitative detection of the IgM, IgA, and IgG antibodies against SARS-CoV-2 (Stieber et al, 2020). The results of this study need further independent evaluation, but if more researchers can continue to improve the detection accuracy of the LFIA, this method will display greater commercial application value.…”
Section: Lateral Flow Immunoassaymentioning
confidence: 99%
“…Fortunately, the move towards point of care COVID testing is now well underway with the development of both immunoassay and rapid-antigen (RAT) COVID-19 RATs [88]. Field testing of these COVID-19 RATs have correlated results with laboratory-based RT-PCR testing, reaching 99-100% specificity, 22-100% sensitivity [89][90][91][92][93][94][95][96][97] and their epidemiological outcomes can be comparable to that of PCR [43]. With the use of COVID-19 RATs increasing to up to 87% [98] of COVID-19 of tests, it has been proposed that a 100% COVID-19 RAT test regime should be acceptable [43].…”
Section: Rdts For Improved Detection Of Covid-19 In Rural and Remote ...mentioning
confidence: 99%